Canaloplasty versus Nonpenetrating Deep Sclerectomy: 2-Year Results and Quality of Life Assessment - Anna Byszewska; Anselm Jünemann; Marek Rękas (Journal of Ophthalmology)
Purpose. To compare phacocanaloplasty (PC) and phaco-non-penetrating deep sclerectomy (PDS). Methods. 75 patients with uncontrolled glaucoma and cataract were randomized for PC (37 eyes) or PDS (38 eyes). Intraocular pressure (IOP) and number of medications (meds) were prospectively evaluated. Follow-up examinations were performed on days 1 and 7 and after 1, 3, 6, 12, 18, and 24 months. Surgical success was calculated. Complications and postoperative interventions were noted. Quality of life (QoL) was analyzed. Results. Preoperatively, mean IOP and meds were comparable (P>0.05). After 24 months, IOP significantly decreased in PC from 19.4 ± 5.9 mmHg (2.6 ± 0.9 meds) to 13.8 ± 3.3 mmHg (0.5 ± 0.9 meds) and in PDS from 19.7 ± 5.4 mmHg (2.9 ± 0.9 meds) to 15.1 ± 2.9 mmHg (1.1 ± 1.2 meds). Statistically lower IOP was observed in PC in the 6th month and persisted until 24 months (P<0.05). No difference was found in meds (except for month 18, in which less drugs were used in PC (P=0.001)) or success rates (P>0.05). The most frequent complication in PC was transient hyphema (46%), in PDS bleb fibrosis (24%). PC patients during postoperative period required only goniopuncture (22% of subjects), whereas PDS patients required, in order to maintain subconjuctival outflow, subconjunctival 5-fluorouracil injections in 95% of cases (median = 3), suture lysis (34%), needling (24%), and goniopuncture (37%). NEI VFQ-25 mean composite score for PC was 78.04 ± 24.36 points and for PDS 74.29 ± 24.45 (P=0.136). α Cronbach’s correlation coefficient was 0.913. Conclusions. PC leads to a more effective decrease in IOP than PDS in midterm observation with similar safety profiles. PDS patients required a vast number of additional procedures in contrast to PC patients, but this fact did not influence QoL.